2015
DOI: 10.1136/bjophthalmol-2015-307600
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of temple-related problems following lateral wall rim-sparing orbital decompression for thyroid-related orbitopathy

Abstract: This is the first paper to show that persistent, troublesome temple-related problems following LWRS orbital decompression can be surgically corrected. Patients should be counselled about the potential risk of these complications when considering LWRS orbital decompression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 21 publications
0
10
0
1
Order By: Relevance
“…In recent years, lateral wall bony decompression for TRO has become the first surgical option for many surgeons [12]. Recent studies [5] have shown that DLW decompression (including removal of the greater wing of the sphenoid bone) allows a bigger decompression than that obtained with the traditional lateral wall bony decompression or the paranasal sinuses decompression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, lateral wall bony decompression for TRO has become the first surgical option for many surgeons [12]. Recent studies [5] have shown that DLW decompression (including removal of the greater wing of the sphenoid bone) allows a bigger decompression than that obtained with the traditional lateral wall bony decompression or the paranasal sinuses decompression.…”
Section: Discussionmentioning
confidence: 99%
“…Various techniques and approaches have been described for deep lateral wall (DLW). Bony decompression of the orbit, including coronal approach [7], superior crease [812], canthotomy [13, 14], transconjunctival “swinging eyelid” [15], and lateral triangle flap technique [16]. It can be described more simply, when the procedure is performed by an ab interno approach, removing [9] or not removing [11, 17, 18] the orbital rim or ab externo with [5, 12, 1921] or without rim sparing [10, 21].…”
Section: Introductionmentioning
confidence: 99%
“…However, complications such as visible asymmetry, temporal hollowing, or masticatory oscillopsia were reported with this technique [22]. “Rim sparing” decompression was later described; oscillopsia and temporal wasting can occur with this approach as well, though perhaps less frequently [23, 24]. Leaving a thin rim of bone overlying the temporalis muscle has been suggested as a means to prevent these complications [25].…”
Section: Discussionmentioning
confidence: 99%
“…Five of our patients have undergone fat transplantation to correct the defect, either by injection of fat (three patients) or by using a dermis-fat-graft (two patients). In a recent series of 11 patients with temporal hollowing, Siah et al (2015) used different modalities for correction including Medpore implants, and injections of autologous fat and synthetic fillers. In a recent series of 11 patients with temporal hollowing, Siah et al (2015) used different modalities for correction including Medpore implants, and injections of autologous fat and synthetic fillers.…”
Section: Discussionmentioning
confidence: 99%
“…McNichols et al (2012) suggested that dermis-fat-graft should be used for correcting temporal hollowing. In a recent series of 11 patients with temporal hollowing, Siah et al (2015) used different modalities for correction including Medpore implants, and injections of autologous fat and synthetic fillers.…”
Section: Discussionmentioning
confidence: 99%